2007
DOI: 10.1016/j.jacc.2006.11.034
|View full text |Cite
|
Sign up to set email alerts
|

The Reno-Protective Effect of Hydration With Sodium Bicarbonate Plus N-Acetylcysteine in Patients Undergoing Emergency Percutaneous Coronary Intervention

Abstract: Rapid intravenous hydration with sodium bicarbonate plus N-AC before contrast injection is effective and safe in the prevention of CIN in patients undergoing emergency PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(165 citation statements)
references
References 33 publications
6
153
1
4
Order By: Relevance
“…Posterior studies evaluated sodium bicarbonate in the prevention of CIN in patients submitted to the angiography and/or PCI produced conflicting results [17][18][19][20][21][22][23] . Some of these studies evaluated the use of sodium bicarbonate plus N-acetylcysteine 17,19,21,23 and, therefore, do not allow for a definitive conclusion regarding the benefit of isolated sodium bicarbonate in CIN prophylaxis, once the evaluation of two drugs simultaneously is an important confusion bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Posterior studies evaluated sodium bicarbonate in the prevention of CIN in patients submitted to the angiography and/or PCI produced conflicting results [17][18][19][20][21][22][23] . Some of these studies evaluated the use of sodium bicarbonate plus N-acetylcysteine 17,19,21,23 and, therefore, do not allow for a definitive conclusion regarding the benefit of isolated sodium bicarbonate in CIN prophylaxis, once the evaluation of two drugs simultaneously is an important confusion bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies evaluated the use of sodium bicarbonate plus N-acetylcysteine 17,19,21,23 and, therefore, do not allow for a definitive conclusion regarding the benefit of isolated sodium bicarbonate in CIN prophylaxis, once the evaluation of two drugs simultaneously is an important confusion bias. Among studies that compared only sodium bicarbonate and saline solution, the results are also inconsistent 18,20,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 14 randomized trials, including 2290 patients, compared sodium bicarbonate with sodium chloride for the prevention of CI-AKI and satisfied our selection criteria. Eight trials have been published (7,8,(15)(16)(17)(18)(19)(20) and six remain unpublished (21)(22)(23)(24)(25)(26)(27). The unpublished studies were identified in abstract form.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…In this study, both groups were given sodium chloride at the same rate pre-and postcontrast exposure; however, the sodium bicarbonate group received a single 20-mEq bolus of sodium bicarbonate immediately before contrast exposure. All other trials identified in the systematic review administered sodium bicarbonate as an infusion of at least 5 h. The study by Recio-Mayoral was also excluded from the analysis (20). In this trial, the sodium bicarbonate group received more volume than the sodium chloride group (20).…”
Section: Eligible Studiesmentioning
confidence: 99%